Challenges and opportunities in coding the commons: problems, procedures, and potential solutions in large-N comparative case studies - Ratajczyk, Elicia; Brady, Ute; Baggio, Jacopo A.; Barnett, Allain J.; Perez-Ibara, Irene; Rollins, Nathan; Rubiños, Cathy; Shin, Hoon C.; Yu, David J.; Aggarwal, Rimjhim; Anderies, John M.; Janssen, Marco A. (International journal of the commons, 2016)
On-going efforts to understand the dynamics of coupled social-ecological systems and common pool resources have led to the generation of numerous datasets based on a large number of case studies. This data has facilitated the identification of important factors and fundamental principles thereby increasing our understanding of such complex systems. However, the data at our disposal are often not easily comparable, have limited scope and scale, and are based on disparate underlying frameworks which inhibit synthesis, meta-analysis, and the validation of findings. Research efforts are further hampered when case inclusion criteria, variable definitions, coding schema, and intercoder reliability testing are not made explicit in the presentation of research and shared among the research community. This paper first outlines challenges experienced by researchers engaged in a large-scale coding project; highlights valuable lessons learned; and finally discusses opportunities for future comparative case study analyses of social-ecological systems and common pool resources.